2006
DOI: 10.1111/j.1368-5031.2006.00742.x
|View full text |Cite
|
Sign up to set email alerts
|

Bax, bcl-2 and c-kit expression in non-small-cell lung cancer and their effects on prognosis

Abstract: In non-small-cell lung cancer (NSCLC), stage of the disease is still the most important prognostic factor. Other than stage, many biological markers and many other prognostic factors are studied to define their effects on prognosis of lung cancer. In this study, we aimed to evaluate the expressions of Bax and bcl-2 genes which are important in apoptosis and c-kit, which is a tyrosine kinase transmembrane receptor, as well as searched their response to treatment modalities and effects on survival. Sixty-nine NS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
1
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 40 publications
2
17
1
2
Order By: Relevance
“…Bcl-2 expression has been confirmed in 20% to 58% of NSCLC and 32% to 69.4% of squamous cell carcinomas of the lung [19,22,28] and this is consistent with our findings of 50% and 51% Bcl-2 positive NSCLC tumors and 62% and 63% positive squamous cell carcinomas for the training and validation cohorts respectively. Bcl-2 has been found to mediate the anti-apoptotic effect of nicotine in lung cancer [44] and we observed higher Bcl-2 expression in tumors of smokers (n = 265) compared to non smokers (n = 29; mean ± SE 30.8 ± 2.1 and 22.7 ± 2.96 respectively; data not shown) however this did not reach statistical significance due to small number of non smokers.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Bcl-2 expression has been confirmed in 20% to 58% of NSCLC and 32% to 69.4% of squamous cell carcinomas of the lung [19,22,28] and this is consistent with our findings of 50% and 51% Bcl-2 positive NSCLC tumors and 62% and 63% positive squamous cell carcinomas for the training and validation cohorts respectively. Bcl-2 has been found to mediate the anti-apoptotic effect of nicotine in lung cancer [44] and we observed higher Bcl-2 expression in tumors of smokers (n = 265) compared to non smokers (n = 29; mean ± SE 30.8 ± 2.1 and 22.7 ± 2.96 respectively; data not shown) however this did not reach statistical significance due to small number of non smokers.…”
Section: Discussionsupporting
confidence: 91%
“…Meta-analysis of 13 immunohistochemical studies assessing Bcl-2 with the same antibody clone as used in this study revealed that Bcl-2 was associated with better survival for NSCLC patients (HR = 0.71, 95% CI 0.61-0.83) however this study was biased in favor of positive trials [22]. Bcl-2 has also been reported to be a negative prognostic marker [32,33,35,36,43] whereas the majority of studies on Bcl-2 expression show no impact on survival [20,21,27,28]. Methodology differences in immunohistochemistry, different thresholds for Bcl-2 and use of conventional semi-qualitative, subjective pathologist-scoring systems, lack of reproducibility and lack of independent validation of the results preclude firm conclusions based on the current literature.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Our data showing that non-smokers have lower Bcl-2 mRNA expression than smoking NSCLC patients suggests the hypothesis that part of the pre-disposition of smokers for lung cancer may be due to an up-regulation of Bcl-2 expression by some component(s) of the smoke. However, other studies have not reported an association between smoking and Bcl-2 expression [21,30]. Even though in our study Bcl-2 expression and smoking were associated, smoking was no prognostic factor in NSCLC after curative resection.…”
Section: Discussioncontrasting
confidence: 82%
“…However, mutation status of KIT was not examined in that study. Regarding the KIT expression in lung cancer, Yaren et al [19] have reported that KIT immunostaining was relatively rarely positive in squamous cell carcinoma of the lung (2 of 36 cases; 5.6%) and in adenocarcinoma of the lung (2 of 28 [11]. They reported that 19 of 22 thymic cancers revealed positive staining for KIT, whereas none of 110 thymomas contained positive cells.…”
Section: Discussionmentioning
confidence: 95%